Surface plasmon polariton pulse shaping via two-dimensional Bragg grating pairs - Crampton Kevin T.; Joly Alan G.; El-Khoury Patrick Z. (Nanophotonics, 2020)
We demonstrate control over the spatial and temporal properties of surface plasmon polaritons (SPPs) launched from nanohole arrays in silver. The arrays provide wave vector matching to allow the conversion of free-space photons into counter-propagating SPPs. SPPs launched from multiple arrays interfere at well-defined spatial positions, and the interference fringes form an all-SPP periodic nano-optical grating which evolves in space and time as the SPPs propagate. The spatio-temporal characteristics of the optical grating can be tuned through various nanohole array parameters such as tilt angle, separation, and array width. In addition, we examine multiperiodic arrays (MPAs) consisting of arrays with different pitches placed adjacent to one another. This platform allows the temporal interference of SPPs with different central wavelengths to be tailored through the MPA geometric and structural parameters. The temporal interference serves as an encoded signal, whereby the frequency components can be controlled by the array properties.